Delayed Treatment with α-Phenyl-N-tert-butyl Nitrone (PBN) Attenuates Secondary Mitochondrial Dysfunction after Transient Focal Cerebral Ischemia in the Rat - Satoshi Kuroda; Ken-ichiro Katsura; Lars Hillered; Timothy E. Bates; Bo K. Siesjö (Neurobiology of Disease, 1996)
The present experiments were undertaken to explore the mechanisms of secondary brain damage in focal ischemia of long duration (2 h), followed by recirculation. Recirculation has previously been found to cause partial recovery and secondary deterioration of cellular bioenergetic state, the subsequent damage being ameliorated by a free radical spin trap, α-phenyl-N-tert-butyl nitrone (PBN), even when the drug was given 1 (or 3) h after the start of recirculation. Our objective was to assess whether the secondary deterioration of the cellular bioenergetic state is due to mitochondrial dysfunction and to study whether PBN acts by preventing secondary damage to mitochondria. Focal and perifocal (“penumbral”) tissues were sampled after 2 h of ischemia and after 1, 2, and 4 h of recirculation; at the latter two times, vehicle- and PBN-injected animals were studied, PBN being given after 1 h of recirculation. Homogenates were prepared, and stimulated (+ADP), nonstimulated (−ADP), and uncoupled respiratory rates were measured polarographically. The results were similar in focus and penumbra, albeit more pronounced in the focus. Ischemia was associated with a decrease in ADP-stimulated and uncoupled respiration rates, with a marked fall in the respiratory control ratio, defined as ADP-stimulated divided by nonstimulated respiration. Recirculation (1 h) brought about partial recovery, but continued reflow (2 and 4 h) was associated with a secondary deterioration of respiratory functions. This deterioration was prevented by PBN, given 1 h after the start of recirculation. The results raise the question whether the secondary deterioration of the cellular bioenergetic state in focal ischemia–reperfusion is due to secondary mitochondrial dysfunction and whether the amelioration of the subsequent damage by PBN is partly or wholly due to the effect of the spin trap on the mitochondria.